Age-Related Arterial Stiffening Is Associated with a Body Shape Index and Lean Body Mass Index: A Retrospective Cohort Study in Healthy Japanese Population - Daiji Nagayama; Yasuhiro Watanabe; Kentaro Fujishiro; Kenji Suzuki; Masahiro Ohira; Kohji Shirai; Atsuhito Saiki (Obesity Facts)
Introduction: Several anthropometric indices reflecting cardiometabolic risks have been developed, but the relationship of body composition with arterial stiffness remains unclear. We aimed to determine the interaction between age-related anthropometric changes and progression of arterial stiffness. Methods: This research analyzed cross-sectional data (N = 13,672) and 4-year longitudinal data (N = 5,118) obtained from a healthy Japanese population without metabolic disorders. The relationship of age with anthropometric indices comprising estimated lean body mass index (eLBMI), body mass index (BMI), waist circumference (WC), and a body shape index (ABSI) was examined. The mediating effects of the indices on the association between age and arterial stiffness assessed by cardio-ankle vascular index (CAVI) were analyzed. Results: Unlike BMI and WC, ABSI (Rs = 0.284) and CAVI (Rs = 0.733) showed a positive linear relationship with aging in stratified analyses. Especially in the middle-older age groups, eLBMI showed a declining trend with aging. An increase in ABSI was associated with a decrease in eLBMI, whereas increase in BMI or WC was related to increased eLBMI. In cross-sectional analyses, age was associated with CAVI, partially mediated by ABSI or eLBMI after adjusting confounders. Baseline CAVI correlated negatively with 4-year change in (Δ)eLBMI (Rs = −0.120 in men, −0.161 in women). ΔCAVI correlated negatively with ΔeLBMI (Rs = −0.031). Conclusion: ABSI is a modifiable index that well reflects age-related changes in arterial stiffness and body composition including lean body mass. Since arterial stiffening may cause skeletal muscle loss, potentially creating a vicious cycle, prioritizing CAVI and anthropometric indices in clinical practice may be a useful strategy.